An evolving risk landscape: Insights from a decade of surveys of executives and risk professionals - Mark S. Beasley; Bruce Branson; Don Pagach (Journal of Risk and Financial Management, 2023)
We report on the results obtained from ten annual surveys of global business executives on their perceptions of the most significant risks facing their organizations in the ensuing calendar year. These surveys of C-suite executives, directors and other risk professionals elicit their concerns about risks that may affect their organization's success over the near-term horizon (i.e., the next calendar year). After a decade, we believe these results provide an opportunity to examine how the global risk landscape has evolved. In addition, two additional survey questions allow us to examine how these executives view the overall risk context and how enterprise risk management (ERM) is deployed and augmented in the face of an escalating risk environment. On average, we find that executives view the risk landscape they face as persistently risky over the ten-year period, even during the relatively robust economic environments for much of that time frame. Two industries report much more volatility in their risk environments, with respondents from the Healthcare sector and in Technology, Media and Telecommunications acknowledging the largest volatility. We also observe an increase in entities' decisions to devote more time and resources to risk management over the ten-year period, suggesting that ERM has become an essential mechanism for organizational success. Our goal is to highlight the realities of constantly changing risk conditions and how context (e.g., industry and time) is an important distinguishing factor that affects an organization's given risk profile, which is relevant to both executives and academics. Collectively, our findings emphasize the importance of understanding the ever-changing context of an organization's environment, that risk identification must be an ongoing process, and that there is no "one-size-fits-all" approach to risk governance. We believe all this signals the importance of future research to help organizations respond with robust risk governance.
Keywords: 650; enterprise risk management; risk assessment; risk identification; risk survey